Nannochloropsis spp. as Feed Additive for the Pacific White Shrimp: Effect on Midgut Microbiology, Thermal Shock Resistance and Immunology - Ariane Martins Guimarães; Cristhiane Guertler; Gabriella do Vale Pereira; Jaqueline da Rosa Coelho; Priscila Costa Rezende; Renata Oselame Nóbrega; Felipe do Nascimento Vieira (Animals, 2021)
This work aimed to evaluate Nannochloropsis spp. as feed additive in the diet of Pacific white shrimp for their effect on midgut microbiology, thermal shock resistance and immunological parameters. Initially, the digestibility of the microalgae meal was assessed, and the apparent digestibility coefficient (ADC) was determined. The ADC was, in general, high in lipids (78.88%) and eicosapentaenoic fatty acid (73.86%). Then, Nannochloropsis spp. were included in diets at four levels (0, 0.5, 1 and 2% inclusion). The shrimp were reared in 500 L clear water tanks containing 20 shrimp per tank with an initial weight of 6.05 ± 0.06 g and fed four times a day. Shrimp fed with supplemented diets containing Nannochloropsis spp. (0.5 and 2%) presented higher resistance to thermal shock when compared to the non-supplemented group (control). Shrimp fed with 1 and 2% of algae inclusion had a higher production of reactive oxygen species (ROS) when compared to other treatments. No statistical difference was observed in the immunological parameters and microbiology of the intestinal tract. Thus, the inclusion of Nannochloropsis spp. in shrimp diets at 0.5 and 2% levels increases resistance to thermal shock and ROS production in shrimp.